The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2021.658669
|View full text |Cite
|
Sign up to set email alerts
|

The Establishment of New Thresholds for PLND-Validated Clinical Nomograms to Predict Non-Regional Lymph Node Metastases: Using 68Ga-PSMA PET/CT as References

Abstract: PurposePLND (pelvic lymph node dissection)-validated nomograms are widely accepted clinical tools to determine the necessity of PLND by predicting the metastasis of lymph nodes (LNMs) in pelvic region. However, these nomograms are in lacking of a threshold to predict the metastasis of extrareolar lymph nodes beyond pelvic region, which is not suitable for PLND. The aim of this study is to evaluate a threshold can be set for current clinical PLND-validated nomograms to predict extrareolar LN metastases beyond p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(67 reference statements)
0
4
0
1
Order By: Relevance
“…Notwithstanding, a previous study showed that patients with high-risk disease who may benefit from a super-extended PLND can be identified with the nomograms themselves, but with a higher cutoff point in the risk for metastasis when compared to those currently advocated by some guidelines (30% vs. 5% or 7%) 23 , 24 , 27 . Similarly, another study observed that risk greater than 60% better identified patients with benefit from extended PLND, most of whom had non-regional metastasis 28 . Therefore, the present results reinforce the need for a more refined recommendation of the extension of the PLND in function of the risk of lymph node metastasis and, perhaps, intraoperative analysis of the lymph nodes in selected patients in order to perform a super-extended approach when necessary.…”
Section: Discussionmentioning
confidence: 89%
“…Notwithstanding, a previous study showed that patients with high-risk disease who may benefit from a super-extended PLND can be identified with the nomograms themselves, but with a higher cutoff point in the risk for metastasis when compared to those currently advocated by some guidelines (30% vs. 5% or 7%) 23 , 24 , 27 . Similarly, another study observed that risk greater than 60% better identified patients with benefit from extended PLND, most of whom had non-regional metastasis 28 . Therefore, the present results reinforce the need for a more refined recommendation of the extension of the PLND in function of the risk of lymph node metastasis and, perhaps, intraoperative analysis of the lymph nodes in selected patients in order to perform a super-extended approach when necessary.…”
Section: Discussionmentioning
confidence: 89%
“…For patients with regional LNMs, RP±PLND should be performed. PSMA-PET/CT can be used to exclude patients with distal LNMs (M1a stage), bone metastases (M1b stage), or visceral metastases (M1c stage) from planned curative radical prostatectomy 28 . For LNMs with a diameter ≥2.3 mm, PSMA-PET can achieve a detection rate of 50.0% 29 .…”
Section: Selecting Proper Candidates For Psma-targeted Surgerymentioning
confidence: 99%
“…Előbbi szenzitivitása 85, specificitása 98%-osnak adódott, szemben az utóbbi 38 és 91%-os értékeivel (15). A sebészi kezelési tervvel kapcsolatban a PSMA-PET/CT jelentős változáshoz vezethet azon tulajdonságának köszönhetően, hogy kicsi, de PSMA-avid nyirokcsomókat detektálhat a medencerégióban a tervezett beavatkozás kiterjedésén túli területen (16). Definitív sugárkezelés előtt végzett PSMA-PET/CT alkalmazhatónak látszik a domináns intraprosztatikus lézió kijelölésére és a biológiai besugárzási céltérfogat azonosítására, beleértve a konvencionális vizsgálómódszerekkel nem azonosítható nyirokcsomóáttétek tisztázását is (2).…”
Section: Rövidítés Mip=maximum Intenzitásprojekció Lokális Recidívát ...unclassified